Fish exposed to eprinomectin show hepatic oxidative stress and impairment in enzymes of the phosphotransfer network - Serafini S.* (2019)
© 2019The objective of this study was to evaluate whether the antiparasitic drug eprinomectin causes hepatic oxidative stress and impairment of hepatic energetic metabolism in the silver catfish (Rhamdia quelen), in conditions of experimental aquatic contamination. The fish were exposed for 24 and 48 h at various concentrations of eprinomectin (0.0, 1.124, 1.809 and 3.976 μg L−1), followed by 48 h of recovery in eprinomectin-free water. We measured levels of reactive oxygen species (ROS) and lipoperoxidation (LOOH) in hepatic tissue, as well as levels of antioxidant capacity against peroxyl radicals (ACAP), and activities of the antioxidant enzymes superoxide dismutase (SOD), glutathione peroxidase (GPx) and glutathione S-transferase (GST), in addition to the activities of enzymes involved in energy metabolism, adenylate kinase (AK) and pyruvate kinase (PK). After 24 h, hepatic ROS levels increased in fish exposed to all concentrations of eprinomectin, and the same occurred with LOOH at the two highest concentrations of eprinomectin. ACAP levels decreased after 24 h of exposure to the highest concentration, also occurring with SOD activity at the two highest concentrations. Glutathione enzymes activities (GPx and GST) decreased after 48 h of exposure to the highest concentration. Fish transfer to eprinomectin-free water, with re-analysis after 48 h post-recovery, was unable to reverse ROS and LOOH increases, likewise with the reductions of ACAP, SOD, GPx and GST, especially at the two highest concentrations. AK and PK activities decreased after 48 h of exposure, AK decreased at the two highest concentrations and PK decreased at the highest concentration. AK activity remained lower after 48 h in eprinomectin-free water. PK activity returned to normal after 48 h in eprinomectin-free water. In summary, silver catfish exposed to aquatic contamination with the antiparasitic drug eprinomectin showed hepatic oxidative stress, possibly related to impairment of the phosphotransfer network and energy metabolism.